2021
DOI: 10.1177/0956462421997193
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis among men who have sex with men attending a large HIV clinic in Trinidad

Abstract: A chart review study was conducted to determine the prevalence of syphilis and explore the associated risk factors among men who have sex with men (MSM) who attended a large HIV clinic in Trinidad during the period January–December 2019. Patients were routinely screened for syphilis annually, and demographic, clinical, and laboratory data were extracted from the medical records. Descriptive and bivariate analyses were performed, and factors significantly associated with a syphilis diagnosis were assessed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…In this study, the prevalence of syphilis in MSM living with HIV was 28% and MSM with a previous diagnosis of syphilis were five times more likely to be diagnosed with syphilis (OR 5.16; 95% CI, 1.03–25.83). These findings are similar to a retrospective analysis in MSM living with HIV conducted at the MRFTT in 2019 which found a high prevalence of syphilis of 41.3% [ 11 ] and patients with a previous history of treated syphilis were ten times more likely to be diagnosed with syphilis [ 11 ]. Similar results were demonstrated by Roth et al in a study of a Swiss cohort of MSM living with HIV where repeat episodes of syphilis were reported [ 15 ] and this was attributed to high risk sexual behavior and the high background rate of syphilis in MSM populations [ 15 ].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In this study, the prevalence of syphilis in MSM living with HIV was 28% and MSM with a previous diagnosis of syphilis were five times more likely to be diagnosed with syphilis (OR 5.16; 95% CI, 1.03–25.83). These findings are similar to a retrospective analysis in MSM living with HIV conducted at the MRFTT in 2019 which found a high prevalence of syphilis of 41.3% [ 11 ] and patients with a previous history of treated syphilis were ten times more likely to be diagnosed with syphilis [ 11 ]. Similar results were demonstrated by Roth et al in a study of a Swiss cohort of MSM living with HIV where repeat episodes of syphilis were reported [ 15 ] and this was attributed to high risk sexual behavior and the high background rate of syphilis in MSM populations [ 15 ].…”
Section: Discussionsupporting
confidence: 87%
“…In our study, most of the syphilis infections were asymptomatic (89.2%). This was also reported in the retrospective study of MSM attending the HIV Clinic in Trinidad in 2019 with 71.1% of these infections being asymptomatic [ 11 ] and by Branger et al [ 17 ] in an outpatient clinic in Amsterdam where routine syphilis screening conducted on 1,105 HIV infected patients identified 81 cases with syphilis, all among males of whom 94% were MSM with 33% of the infections being asymptomatic. A few studies have suggested that persons with past episodes of syphilis were more likely to be asymptomatic on repeat episodes [ 18 , 19 ] possibly due to the acquired immune response resulting from past infection which may attenuate the clinical manifestations of reinfection with T .…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations